Biostratigraphy and Depositional Environment of Early to Middle Miocene Sediments at Kulon Progo, Wonosari, and Punung Areas Based on Their Foraminiferal and Palynological Assemblages - Rakhmat Fakhruddin (Indonesian Journal on Geoscience, 2019)
DOI: 10.17014/ijog.6.1.73-101Epiclastic sediments at Kulon Progo, Wonosari, and Punung areas were deposited in marine and terrestrial environments. The aim of this study is to reconstruct biostratigraphy, depositional environments, and sequence stratigraphy of several sections of these epiclastic sediments. Combined foraminiferal and palynological analysis needs to be done to better understand the age correlation of epiclastic sediments of those three studied areas. Epiclastic sediments at Wonosari area (Sambipitu Formation) were deposited at N7-N8 zones, late Early Miocene, while at Kulon Progo area (lower part of Jonggrangan Formation) and Punung area (Jaten, Wuni, and Nampol Formations) were deposited at Middle Miocene. Sediments of the lower part of Jonggrangan Formation were deposited in various environments: mangrove and inner to middle shelf. Depositional environments at the lower part of Sambipitu Formation at Kali Ngalang section are peat swamp and mangrove environments which are more landward compared to the upper part of sediments of Sambipitu Formation which were deposited in marine environments: inner shelf, middle shelf, and outer shelf. At Punung area, the depositional environments are riparian forest, alluvial swamp, backmangrove, mangrove, and inner shelf. MFS-A and MFS-B at Wonosari area found in N8 zone, late Early Miocene, were made as a regional datum correlation for this area, because they are the good age control as they show low diachronous. MFS-1 and MFS-2 at Kulon Progo and Punung areas are found in Florschuetzia meridionalis zone, Middle Miocene.